THE TRAILER AS A PHENOMENON OF CONTEMPORARY SCREEN CULTURE / ТРЕЙЛЕР КАК ФЕНОМЕН СОВРЕМЕННОЙ ЭКРАННОЙ КУЛЬТУРЫ - BULANOV E.V. / БУЛАНОВ Е.В. (Наука телевидения, 2017)
The author considers a special kind of movie advertising, —the trailers of the films, preparing for the release. This format has its own characteristics, the genre, the style and the uniqueness of the individual phenomenon of contemporary screen culture. It is a rapidly growing format, which is, increasingly, separated from its source and lives its own life, becoming for most culturally significant event due to the special structure, dynamics, clipvote, saturation of emotions and events, archetypal characters that are relevant to the viewer.